MICROBIOLOGICAL SUITABILITY OF AFRICAN BITTER YAM STARCH - wuagwu, M A I; Akerele, J 0 (Biological Sciences - PJSIR, 2001)
Starch was extracted from African Bitter Yam (Dioscorea dumetorum) and its physical properties were determined. Its ability to support growth of microorganisms was assessed and compared with maize starch BP. Both starches were used to prepare compressed tablets by wet granulation method. Some physical characteristics of the tablets were determined. The tablets were further tested for the ability to support microbial growtb soon after production and after storage at ambient conditions for four weeks. Both starches as well as lactose tablets containing them did not support the growth of coliform organisms and Salmonella species. Maize starch BP supported growth of microorganisms more than African Bitter Yam starch. All the tablets complied with the British Pbarmacopoea standards for uncoated tablets. Tablets containing maize starch BP and those containing African Bitter Yam starch did not support the growth of coliform organisms and Salmonella species. Tablets containing Yam starch supported much less microbial growth than those of maize starch BP. It is inferred that African Bitter Yam starch can be considered as pharmaceutical grade starch.